DI-016 Prevention of toxoplasmic encephalitis and pneumocystis jiroveci pneumonia in patients infected with HIV: Efficacy and safety of dapsone/pyrimethamine/leucovorin. (14th February 2016) - Valcarce, N; Alvarez, H; Mariño, AI; Casás, A; Montero, AM; Rodríguez, I
Abstract : Background: In HIV infected patients, adverse effects of trimethoprim/sulfamethoxazole (TMP/SMX) involving the skin and bone marrow are frequently observed. An alternative primary prophylaxis regimen against Pneumocystis jiroveci pneumonia (PCP) and toxoplasma encephalitis (TE) should be considered in these settings. Purpose: To evaluate the efficacy and safety of dapsone 50 mg daily+(pyrimethamine 50mg+leucovorin 25 mg) weekly (DPL) as primary prophylaxis of PCP and TE in patients with HIV infection which developed intolerance to TMP/SMX. Material and methods: We performed a retrospective observational study between September 2013 and December 2014. Patients included were chronically infected with HIV, had a CD4 count <200 cells/mm 3, positive IgG antibodies against Toxoplasma and were intolerant to TMP/SMX. We analysed demographic and laboratory data, CDC stage at inclusion, antiretroviral therapy (ART), CD4 count at the beginning and end of DPL, mean time receiving DPL and adverse events, using outpatient electronic medical and pharmacological dispensation records. Before starting dapsone, glucose-6-phosphate dehydrogenase deficiency was ruled out. The indication for discontinuation was CD4 >200 cells/mm 3 for >3 months. We reviewed DHHS, EACS, BHIVA and GESIDA clinical guidelines for supportive scientific evidence. An off-label use form was requested from the hospital pharmacy to prescribe DPL. Results: Three patients were included for a total of 469 HIV infected patients followed in our hospital. All were male, mean age 48 years, and CDC stages A2, B3 and C3, respectively. All were receiving ART (two nucleoside (tide) analogues and one protease inhibitor). CD4 count at the beginning and end of DPL were 119 and 296 cells/mm 3, respectively. Average duration of DPL treatment was 4 months. No patient developed PCP or TE. The combination DPL was well tolerated and no adverse effects were recorded. Conclusion: The combination of dapsone daily with pyrimethamine and leucovorin weekly was an effective and safe alternative to TMP/SMX for primary prophylaxis of PCP and TE in patients with HIV infection. One limitation of our study was the small size of the sample, scarcely representative to draw definitive conclusions. No conflict of interest.